2022
DOI: 10.3329/bjpt.v29i2.63525
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomy, Autecology And Distribution Of Najas Marina L. (Najadaceae) In Bangladesh

Abstract: Detailed taxonomic description of Najas marina L. including information on flowering and fruiting time, autecology, and distribution in Bangladesh are provided. The diagnostic characters with illustrations and behavioural patterns of different habitats are also provided. Presence of Najas marina in Joydia baor indicates that the water quality of this baor is fairly good and minor human interference of the habitats. Bangladesh J. Plant Taxon. 29(2): 183-191, 2022 (December)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…A large number of aquatic macrophytes have been found of these habitats. Alfasane et al (2010Alfasane et al ( , 2013Alfasane et al ( , 2019Alfasane et al ( , 2020Alfasane et al ( , 2021Alfasane et al ( , 2022Alfasane et al ( , 2023 have been reported 11 species of aquatic macrophytes either as new to science, new records and new occurrence including the present species from Bangladesh. Recently Alfasane et al (2023) reported Elodea canadensis Michx.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A large number of aquatic macrophytes have been found of these habitats. Alfasane et al (2010Alfasane et al ( , 2013Alfasane et al ( , 2019Alfasane et al ( , 2020Alfasane et al ( , 2021Alfasane et al ( , 2022Alfasane et al ( , 2023 have been reported 11 species of aquatic macrophytes either as new to science, new records and new occurrence including the present species from Bangladesh. Recently Alfasane et al (2023) reported Elodea canadensis Michx.…”
Section: Introductionmentioning
confidence: 99%
“…The members of this group mostly in aquatic and cosmopolitan in nature. A total of 8 genera and 14 species have been reported from Bangladesh so far (Alfasane et al, 2010(Alfasane et al, , 2022(Alfasane et al, , 2023Siddiqui et al, 2007) from Hydrocharitaceae. In the present paper, the first report of Elodea nuttallii (Planch.)…”
Section: Introductionmentioning
confidence: 99%